METHODS FOR INTEGRATING INFORMATION EXCHANGE BETWEEN CORPORATE SYSTEMS - Askaraliev, O.; Madaminov, Sh. (ILIM hám JÁMIYET, 2025)
In the field of science and technology, a single standardized algorithm for organizing integrated mutual information exchange has not been developed to date. This article analyzes and studies the issues of integration. In the process, some patterns were identified and an approach was chosen to solve the indicated issues. This approach created an opportunity for mutual information exchange between different systems.